Evaluation of Risk Factors for ADHD and Co-Morbid Psychiatric Disorders Among the Parents of Children With ADHD. Issue 9 (July 2019) - Okan Ibiloglu, Aslihan; Atli, Abdullah; Bulut, Mahmut; Gunes, Mehmet; Demir, Suleyman; Kaya, Mehmet Cemal; Yuksel, Tugba; Sir, Aytekin
Objective: The aim of this study is to investigate the presence of ADHD and other psychiatric disorders among parents with at least one child with ADHD relative to parents with children who do not have ADHD.Method: Eighty five parents of children with ADHD with 68 control parents who had healthy children without ADHD were interviewed for participation in present study. Each parent was evaluated for co-existing psychiatric disorders using the Structured Clinical Interview for the DSM IV Axis I Disorders (SCID I).Results: We found that ADHD and co-morbid psychiatric symptoms were increased in the parents of children with ADHD in comparison with the healthy control group.Conclusion: Psychiatric co-morbidity was more common among the parents of patients with inattentive and combined presentations. Adult ADHD is associated with psychiatric co-morbidities including anxiety disorders, mood disorders, and somatoform disorders as well as substantial role impairment.